Characterization of Irewa in Dorothea Rosa Herliany™s Novel Isinga a Feminism Approach - Zuhri, Nur Arafah; Gultom, Johannes Jefria (Universitas Negeri Medan, 2020)
This study aimed at discovering the characterization of Irewa presented in Dorothea Herliany™s Novel and describe feminism reflected in the characterization of Irewa in the novel .The data of this study were the sentences of characterization of main character found in Isinga novel. The data were collected by using documentation technique. The data were analyzed by using descriptive qualitative analysis. The findings of this study were Irewa™s does, says and other thinks about her character™s described toward feminism. In addition, feminism diverse area of inquiry, dealing with the history of women™s.